PROTOTYPE SISTEM PAKAR UNTUK MENDETEKSI TINGKAT RESIKO PENYAKIT JANTUNG KORONER DENGAN METODE DEMPSTER-SHAFER (Studi Kasus: RS. PKU Muhammadiyah Yogyakarta) - , Elyza Gustri Wahyuni, Drs. Widodo Prijodiprodjo, M.Sc., EE ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Coronary heart disease (CHD) is the most cases that trigger of death in developed countries, The number of patients with this disease have increased every year, the WHO data said that 17.3 million people are estimated decease from cardiovascular in 2008, representing 30% of all global deaths. From the mortality data, are estimated 7.3 million caused by coronary heart disease and 6.2 million due to stroke. People who have not detected with heart disease and experiences heart attack suddeny, it will be very threatening his life. The expert systems can serve as a consultant that gives advice to the users and at once as an assistant to the experts. One way to cope and help detect the risk level of oneâs coronary heart disease, is to create the expert system as media of consulting and monitoring a person so that can minimize the occurrence of heart attacks resulting in death. The Dempster-Shafer method is non monotonis reasoning method is used to look for inconsistencies due to addition or reduction of new facts that will change the existing rules, so that the Dempster-Shafer method enables one safe in doing the expert work. This research aims to apply the Dempster-Shafer uncertainty methods in expert system to diagnose the risk level of oneâs coronary heart disease based on factors and symptom of coronary heart disease The benefits of this research was to know the accuracy of Dempster-Shafer inference engine. The basic approach of knowledge is used in the this expert system is by a Rule-Based Reasoning. The reasoning method is used is forward chaining, the reasoning that is reasoning starts from the risk factors input and the symptoms that are then used to determine the coronary heart disease diagnosis. The results from 10 cases obtained of the Rekamedis PKU Muhammadiyah Hospital Yogyakarta, the percentage obtained by 100% the truth value of predictive diagnostics system according to the knowledge possessed by an expert.